900MHz and 1800MHz Mobile Phone Effect Towards Adult Head in SAR Distribution and SAR in Weight - Kasumawati, Lias; Abidin, W.A.W.Z; Masri, T.; Othman, A.K.; Ade Syaheda Wani, Marzuki; Dayang Azra, Awang Mat; Kuryati, Kipli (IEEE, 2010)
The investigation on the effect of mobile phone towards adult head in Specific Absorption Rate (SAR) Distribution and SAR in Weight is presented in this paper. Finite Different Time-Domain (FDTD) was used to construct adult head modeling with the attachment of monopole antenna and also to do a simulation in obtaining the SAR Distribution and SAR in Weight either 19 or 109 weight value, respectively. From the simulation, the results show that the values of both SAR are small and do not exceed 4W/kg stated by International Commission on Non-Ionizing Radiation Protection (ICNIRP), National Council on Radiation Protection and Measurement (NCRP) and Institute of Electrical and Electronics Engineers (IEEE). The simulation covered 900MHz and 1800MHz frequency with O.6W radiated power.